Social foundations of corporate culture - G. P. Podolian (Ukrainian Cultural Studies, 2018)
The article is devoted to the analysis of the development of corporate culture as a new form of culture. The dynamic processes of the evolution of corporate culture from the time of the appearance of its individual elements at the beginning of the 20th century to the corporatization of many spheres of social life, the practice of implementing mechanisms of corporate social responsibility in the late XX сеntury remain topical for research. Dynamism of the corporate culture formation in the sphere of economic activity in the twentieth century influenced the rapid spread of its values and standards to other public spheres. Corporate culture as a sociocultural regulator gradually comes to the forefront of scientific, practical and cultural discussions. Recognition of culture as the defining basis of corporate culture allows us to consider neocorporativism as interconnected with it. Mutualities of neocorporativism and culture have become the basis for the emergence of the innovative nature of corporate culture with its focus on partnership and the consolidation of the multidirectional interests of key actors in the interaction. An innovative feature of neocorporativism as the main element of corporate culture is the orientation toward voluntary, legitimate alignment of interest groups and the achievement of cooperation, social partnership of participants in equidistant social interaction on mutually beneficial conditions. It is a non-violent means of forming corporate productive orders that fit into a broader democratic spectrum of interests at different levels of society’s life. And in this you can see the social potential of neocorporativism and corporate culture. Like any new phenomenon, corporate culture revealed the ambivalent essence of the initial stages of the emergence of this innovation, showing the emergence of a list of complex moral-psychological and existential problems of human and societies during the period of grandiose changes. The corporatization of social spheres served as the basis for qualitative transformations of organizational, managerial, social and labol relations, opening additional prospects for the realization of social responsibility and integration.